Ecto-5′-Nucleotidase (CD73) Regulates the Survival of CD8+ T Cells - Rosemblatt, Mariana V.; Parra-Tello, Brian; Briceño, Pedro; Rivas-Yáñez, Elizabeth; Tucer, Suat; Saavedra-Almarza, Juan; Hörmann, Pilar; Martínez, Brandon A.; Lladser, Álvaro; Rosemblatt, Mario; Cekic, Caglar; Bono, María Rosa; et al. (Frontiers in Cell and Developmental Biology, 2021)
Ecto-5′-nucleotidase (CD73) is an enzyme present on the surface of tumor cells whose primary described function is the production of extracellular adenosine. Due to the immunosuppressive properties of adenosine, CD73 is being investigated as a target for new antitumor therapies. We and others have described that CD73 is present at the surface of different CD8+ T cell subsets. Nonetheless, there is limited information as to whether CD73 affects CD8+ T cell proliferation and survival. In this study, we assessed the impact of CD73 deficiency on CD8+ T cells by analyzing their proliferation and survival in antigenic and homeostatic conditions. Results obtained from adoptive transfer experiments demonstrate a paradoxical role of CD73. On one side, it favors the expression of interleukin-7 receptor α chain on CD8+ T cells and their homeostatic survival; on the other side, it reduces the survival of activated CD8+ T cells under antigenic stimulation. Also, upon in vitro antigenic stimulation, CD73 decreases the expression of interleukin-2 receptor α chain and the anti-apoptotic molecule Bcl-2, findings that may explain the reduced CD8+ T cell survival observed in this condition. These results indicate that CD73 has a dual effect on CD8+ T cells depending on whether they are subject to an antigenic or homeostatic stimulus, and thus, special attention should be given to these aspects when considering CD73 blockade in the design of novel antitumor therapies.